Insidensi dan Identifikasi Penyakit Layu pada Terong (Solanum melongena L.) di Desa Tanjung Pering, Kabupaten Ogan Ilir, Provinsi Sumatera Selatan - Hamidson, Harman; Adrian, Rian; Umayah, Abu; Gunawan, Bambang (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Hamidson H, Adrian R, Umayah A, Gunawan B. 2022. Insidence and identification of wilt disease in eggplant (Solanum melongena L.) in Tanjung Pering Village, Ogan Ilir Regency, South Sumatera. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 963-973. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Wilt disease of the Fusarium group is a necrotrophic plant disease that has a wide host range and distribution throughout the world. This pathogen can infect at least 408 plant species worldwide. This field practice aims to determine the percentage level and intensity of attack and identify the cause of wilt disease in eggplant in Tanjung Pering Village, North Indralaya District, Ogan Ilir Regency, South Sumatra Province. The method used in this field practice is carried out by conducting a survey or direct observation in the field to calculate the percentage level and intensity of wilt disease attack on eggplant, then identification is carried out at the Phytopathology Laboratory of the Department of Pests and Plant Diseases, and infectious tests are carried out in experimental land to prove pathogens. cause of wilt disease in eggplant. The results of this field, the cause of wilt disease in eggplant in Tanjung Pering Village, North Indralaya District, Ogan Ilir Regency is caused by the fungus Fusarium sp with an average percentage of wilt disease of 42.54% and an average intensity of wilt disease of 40.90% in the field.